Polymorphisms in microRNA genes as predictors of clinical outcomes in colorectal cancer patients - Pardini, Barbara; Rosa, Fabio; Naccarati, Alessio; Vymetalkova, Veronika; Ye, Yuanqing; Wu, Xifeng; di Gaetano, Cornelia; Buchler, Tomas; Novotny, Jan; Matullo, Giuseppe; Vodicka, Pavel (Carcinogenesis, 2015)
Colorectal cancer (CRC) is one of the most frequently diagnosed malignancies worldwide. It is routinely cured by a 5-fluorouracil (5-FU)-based chemotherapy which improves outcomes in patients. We investigated the effect of single nucleotide polymorphisms (SNPs) in two microRNA (miRNA)-encoding genes that have been previously reported as important in prognosis in patients with stage III CRC and treated with 5-FU-based chemotherapy. Two SNPs (rs4919510 in miR-608 and rs213210 in miR-219-1) were genotyped in 1083 CRC patients recruited in the Czech Republic to evaluate their effect on clinical outcomes. Carriers of the variant T allele in rs213210 and receiving 5-FU chemotherapy were associated with a significantly worse survival [hazard ratio (HR) = 2.18; 95% confidence interval (CI): 1.20-3.98; adjusted P = 0.01] and an increased risk of relapse (HR = 1.94; 95% CI: 1.16-3.25; adjusted P = 0.01). After further stratification for tumor grading, stage III patients carrying the G allele of rs4919510 and undergoing adjuvant chemotherapy were at decreased risk of relapse (HR = 0.44; 95% CI: 0.20-0.94; adjusted P = 0.03). The present study confirms that variations in miRNA-encoding genes may be an important factor for modulating CRC prognosis and predicting therapy response.
Keywords: Adenocarcinoma; Colorectal Neoplasms; Polymorphism, Single Nucleotide; Humans; fluoruracil; Antimetabolites, Antineoplastic; lidé středního věku; MicroRNAs; Biomarkers, Tumor; jednonukleotidový polymorfismus; Female; Aged; senioři; lidé; nádorové biomarkery; staging nádorů; Follow-Up Studies; ženské pohlaví; kolorektální nádory; Male; Middle Aged; prognóza; protinádorové antimetabolity; Fluorouracil; adenokarcinom; mikro RNA; Neoplasm Staging; lokální recidiva nádoru; míra přežití; mužské pohlaví; Neoplasm Recurrence, Local; Prognosis; následné studie; Survival Rate